Breaking bad news is a teachable skill in pediatric residents: A feasibility study of an educational intervention. Issue 6 (June 2015) - Reed, Suzanne; Kassis, Karyn; Nagel, Rollin; Verbeck, Nicole; Mahan, John D.; Shell, Richard
Abstract Objective Patients and physicians identify communication of bad news as a skill in need of improvement. Our objectives were to measure change in performance of first-year pediatric residents in the delivery of bad news after an educational intervention and to measure if changes in performance were sustained over time. Methods Communication skills of 29 residents were assessed via videotaped standardized patient (SP) encounters at 3 time points: baseline, immediately post-intervention, and 3 months post-intervention. Educational intervention used was the previously published "GRIEV_ING Death Notification Protocol." Results The intraclass correlation coefficient demonstrated substantial inter-rater agreement with the assessment tool. Performance scores significantly improved from baseline to immediate post-intervention. Performance at 3 months post-intervention showed no change in two subscales and small improvement in one subscale. Conclusions We concluded that breaking bad news is a complex and teachable skill that can be developed in pediatric residents. Improvement was sustained over time, indicating the utility of this educational intervention. Practice implications This study brings attention to the need for improved communication training, and the feasibility of an education intervention in a large training program. Further work in development of comprehensive communication curricula is necessary in pediatric graduate medical education programs.